Knowledge and Practice towards COVID-19 among Students of Al-Bayan University - Khulood S. Salim; Wafaa M. Al attar; Wissam Wardia (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: On 12 March 2020, world health organization (WHO) declared that COVID-19 was a globalpandemic when more than million humans were infected in more than 200 countries in less than four months.To limit its spread, WHO recommended preventive measures such as hand washing frequently, socialdistancing, and face mask wearing. Public knowledge and practice towards the disease is important. Aimof study: We assess the level of knowledge and practices towards COVID-19 among students in Al-BayanUniversity. Method: A cross- sectional study was conducted to gather information regarding the COVID-19related knowledge and practices among undergraduates. This survey was conducted between October 10till October 15,2020. Results:351 students were participated from medical and non- medical colleges bycompleting the questionnaire online. The overall correct answer rate of the knowledge questionnaire was85.71% and 86.22% of them practicing preventive measures according to WHO guidelines and instructionsof ministry of health(MOH). There were no significant differences in knowledge and practices betweenmedical and non-medical. Conclusion: The students have moderate knowledge and appropriate practicestowards COVID-19, this indicates the success and the efficacy of the of campaigns and the advertisementsannounced by WHO and the local MOH.